Case report of a molar-root incisor malformation in a patient with an autoimmune lymphoproliferative syndrome - Alenka Pavlič; Milka Vrecl; Janja Jan; Milan Bizjak; Ana Nemec (BMC, 2019)
Abstract Background Molar-root incisor malformation (MRIM) is a novel dental phenotype likely related to a patient's past medical history. This case aimed to confirm MRIM by histological and scanning electron microscopy (SEM) examination for the first time in a patient diagnosed with autoimmune lymphoproliferative syndrome (ALPS) and to propose a possible link between ALPS and MRIM that could be attributable to abnormally proliferated bone marrow. Case presentation A 12.5-year-old boy with an extensive medical history, including diagnosis of ALPS, was examined clinically and radiologically to elucidate the reason for pain primarily originating from the area of the lower left permanent first molar tooth (PFM; tooth 36). Dental examination and radiographic survey revealed abnormal pulp cavity morphology of all four PFMs, and these were extracted, resolving the dental pain in the patient. The extracted PFMs were subjected to light microscopy, SEM evaluation and mineral density and elemental composition analyses. Histology of two PFMs revealed the presence of dentin-, bone- and cartilage-like tissues with abundant blood vessels occupying the majority of the pulp chamber. The root canals were obliterated with mineralized structures resembling pulp stones. Two different, highly mineralized abnormal tissues filling the majority of the pulp chamber revealed by SEM and confirming the diagnosis of MRIM displayed a mineral density and elemental composition similar to those of enamel and dentin, respectively. Conclusions It appears likely that in addition to the complex medical history during early childhood in the present case, extensive lymphoid infiltrates that are possible in ALPS patients can be regarded as a cofactor in the development of MRIM by exerting considerable pressure on the developing tooth bud and providing cells capable of differentiating into diverse cell types.